Hip, Hip, hooray day! : a Hip & Hop story - Saltzberg, Barney (San Diego : Harcourt, 2002)
Hop has trouble surprising Hip on her birthday.
"Gulliver Books."
Keywords: Birthdays -- Fiction; Hippopotamus -- Fiction; Best friends -- Fiction; Friendship -- Fiction